2020
DOI: 10.1038/s41392-020-00275-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of miR-515-3p and its targets, vimentin and MMP3, as a key regulatory mechanism in esophageal cancer metastasis: functional and clinical significance

Abstract: Metastasis is the main factor of treatment failure in cancer patients, but the underlying mechanism remains to be elucidated and effective new treatment strategies are urgently needed. This study aims to explore novel key metastasis-related microRNAs (miRNAs) in esophageal squamous cell carcinoma (ESCC). By comparing miRNA profiles of the highly metastatic ESCC cell sublines, we established through serial in vivo selection with the parental cells, we found that the expression level of miR-515-3p was lower in E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 48 publications
0
27
0
Order By: Relevance
“…S1a ). 5 Next-generation sequencing of lncRNAs and miRNAs was carried out and our results suggested that the AC005562.1-hsa-miR-29c regulatory axis was significantly altered in invasive and metastatic cells, and the results were confirmed by qRT-PCR (Fig. 1a , Supplementary Fig.…”
mentioning
confidence: 59%
“…S1a ). 5 Next-generation sequencing of lncRNAs and miRNAs was carried out and our results suggested that the AC005562.1-hsa-miR-29c regulatory axis was significantly altered in invasive and metastatic cells, and the results were confirmed by qRT-PCR (Fig. 1a , Supplementary Fig.…”
mentioning
confidence: 59%
“…miR-515-3p directly regulates MMP3 expression by binding to the coding sequence. MMP3 promotes tumor metastasis and thus represents a promising prognostic biomarker and therapeutic strategy in esophageal squamous cell carcinoma ( Hu et al, 2020 ). Rhabdomyosarcoma (RMS) is an aggressive pediatric malignancy of the muscle that includes fusion positive (FP)-RMS harboring PAX3/7-FOXO1 and fusion negative (FN)-RMS commonly with RAS pathway mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Qi et al [ 73 ] showed that the miR-29b/MMP2 axis inhibited cell invasion in vitro , as well as tumor growth in an animal model, indicating its involvement in both tumor development and metastasis. Other members of the MMP protein family, such as MMP3, MMP13, and MMP14, were found to be regulated by miR-515-3p[ 74 ] , miR-375[ 75 ], and miR-133a[ 76 ], respectively.…”
Section: Roles Of Micrornas In Metastasis Of Esccmentioning
confidence: 99%
“…Similarly, SMAD7 can be regulated by miR-424-5p[ 83 ] and miR-106b[ 84 ]. The miR-515-3p/vimentin regulatory axis can reverse EMT and negatively regulate ESCC metastasis[ 74 ]. Another miRNA that targets vimentin, namely, miR-146a, was also reported to suppress ESCC invasion by disrupting fibronectin membrane assembly[ 85 ].…”
Section: Roles Of Micrornas In Metastasis Of Esccmentioning
confidence: 99%
See 1 more Smart Citation